Crude Oil Prices : Predicting Price Differentials Based on Quality - Bacon, Robert; Tordo, Silvana (World Bank, Washington, DC, 2012)
Many developing countries are becoming oil exporters, producing crude oils that often differ markedly in quality from those principally traded. Governments must predict the prices of such crudes, to forecast revenue and evaluate the fairness of the price they receive from companies selling on their behalf. Oil companies, and industry consultants, have models for analyzing price differentials with well-known "marker" crudes, but these models have not been widely known, or adapted to account for increasingly important quality characteristics, such as acidity. This note explains a methodology for price analysis, and a new extension for incorporating acidity, which can have a big effect on the price differential.